STRUKTUR PENYAJIAN TARI SELAMPE PADA DAYAK SAWE DI DESA SEKONAU KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Purwati, Kresensia; Ismunandar, Ismunandar; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was motivated by resercher’s desire to know the structure of Selampe Dance Presentation to Dayak Sawe at Sekonao Village Sekadau Sub-District of SekadauRegency west Kalimantan. The purpose of this study was to described the structure of presentation that has characteristics from it’s movement, music, makeup, and clothing, as well as rhymes in it. The methode used in this research was descriptive with qualitativeresearch form. The approach used was a choreographic approach. The data source inthis research were Mr. Nirus and Mrs. Serina. Based on data anlysis can be concluded asfollows. The presentation structure of selampe dance was arrangement of one unit onepresentation or appearance that has three important parts in the presentation structurethey are, first part, midle part, and last part. The main elements of presentation structureform such as dance movement which mean to illustrates something known as maknawimotion, design of lines on the floor that traversed by dancers, accompaniment music ofrhymes, theme, makeup and clothing.. Hopefully the result of this research can beimplemented in seni budaya on grade X in SMA Negeri 01 Sekadau Hulu to K-13curriculum in order to all the students understand more about dance tradition. Keywords:The Structure of Selampe Dance Presentation.